Exploring Written Artefacts - Quenzer, Jörg B. (Studies in Manuscript Cultures, 2021)
This collection, presented to Michael Friedrich in honour of his academic career at of the Centre for the Study of Manuscript Cultures, traces key concepts that scholars associated with the Centre have developed and refined for the systematic study of manuscript cultures. At the same time, the contributions showcase the possibilities of expanding the traditional subject of 'manuscripts' to the larger perspective of 'written artefacts'.